Intracranial Pressure in Bacterial Meningitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The role of increased intracranial pressure and its effect on cerebral blood flow in the prognosis of children with bacterial meningitis is reviewed from the Division of Child Neurology, Loma Linda U Sch of Med, Loma Linda, CA.